Individual psychotherapy in drug dependence - Kalyoncu, Ayhan; Mırsal, Hasan (Journal of Dependence, 2000)
Pschotherapy of drug dependence has in the past been considered ineffective by most psychiatrists. But nowadays, psychotherapeutic treatments for drug dependence are very widely used. The types of psychotherapy for treating addiction include individual, family, and group psychotherapies, each with a variety of orientations. Also, drug counseling is effective method with used psychotherapy in addiction treatment. In this article, we have reviewed individual psychotherapy in drug dependence.
Keywords: Dependence; psychotherapy; counseling; culture